Political and legal structure of a polis state of European Antiquity - Khankevich, Olga I. (Journal of the Belarusian State University. Law, 2019)
The article deals with the nature of the ancient polis-type state, its governing institutions, ways of regulating public and private life of full-fledged members of the civil community, the particularities of the procedural practice of the Athenian polis and the Roman republican civitas. The author comes to the following conclusions: an ancient European polis-type state, whose internal life was regulated by legal institutions and a democratic system of government, became a huge progress in the state-building of the ancient era; in the polis and civitas there was a normative fixation of the rights and freedoms of polis citizens – ius civile asserted and protected their personal and property rights and interests; the judicial system and related legislation became an organic element of democratic states of antiquity; ancient thinkers laid fair justice and the equal rights of members of the civil community to participate in political, public and religious life, into the foundation for the definition of ancient democracy.